Artificial hair filaments with improved flame retardancy. Issue 18 (7th December 2020) - Youn, Chulmin; Gong, Da Jeong; Yeo, Sang Young
Abstract: In recent decades, the flame retardancy of wigs has improved by combining polymer fibers and flame retardants. Halogen‐based retardants suppress combustion through a radical trap; however, they are harmful to humans and to the environment. Thus, in this study, black wigs were prepared by polysulfone (PSU)‐based fibers through melt spinning process and were compared to that prepared by poly(ethylene terephthalate) (PET)‐based fibers. Different types and amounts of carbon black added during the melt spinning process to produce its color were also investigated to assess its effects on the manufactured wig. The flame retardancy of PSU and PET fibers was evaluated using limited oxygen index (LOI) measurement. The LOI of PET fiber was 24%, while that of PSU fiber was 29%, confirming its highly flame‐retardant behavior. Based on its mechanical properties (tenacity and elongation), PSU fibers (1.5 g/den) are more suitable for artificial human hair due to its higher tenacity than PET fibers (0.8 g/den). The addition of a small amount of carbon black (<0.5 wt%) did not negatively affect the produced wig; thus, a highly flame‐retardant black wig with superior mechanical properties was obtained. Abstract : Polysulfone (PSU), a super engineering plastic, is a highly flame retardant polymer. This was manufactured as a single filament through a melt spinning process. The flame retardancy of PSU fiber is superior to PET fiber, which is mainly used for artificial hair, and prevents melt drip, which is the main cause of secondary fire risk.